(untitled) (Bangladesh Journal of Medicine, 2021)
Introduction: Vitamin D deficiency has been linked to a whole spectrum of diseases including osteoporosis, cancer, diabetes, and cardiovascular and immune disorders. Though Bangladesh is low latitude country, vitamin D Deficiency is serious and wide spread problem in Bangladesh. Physicians of Bangladesh are more vulnerable to low vitamin D status due to long indoor work hours and lack of sunlight exposure in both government & private institute. So, the aim of this study to evaluate vitamin D status among the physicians working around the Bangladesh. Methods: This was a cross-sectional, multicenter study where we enrolled 1112 doctors from 9 different areas of Bangladesh from May 2018 to June 2019. A Blood sample was collected from all participants to measure Serum 25(OH)D and various patient data such as age, gender, BMI, physical activity level during leisure time, use of vitamins and medications, sunlight exposure time, tea/coffee drinking, smoking, H/O comorbidities etc. was collected. Results: Of the 1112 doctors assessed in the study,794 (71.4%) was male and 318 (28.6%) was female. Mean age of the participants was 45.5±11.1 Years. Vitamin D deficiency and insufficiency was found in 734 (65.8%) and 105 (9.4%) participants respectively. Mean vitamin D level was 18.9 ng/ml (±8.6 ng/ml). Less than 5% of participants of Rajshahi, Rangpur, Dhaka, Bogura and Sylhet had sufficient vitamin D level. Vitamin D deficiency was significantly associated with age, obesity, sunlight exposure, physical inactivity, hypertension and vitamin D supplementation. Conclusion: Vitamin D deficiency is very common among physicians of all over Bangladesh. The high prevalence of vitamin D deficiency in the present study points towards urgent need of an integrated approach to detect vitamin D deficiency among health care professionals and treat appropriately. Bangladesh J Medicine January 2021; 32(1) : 31-38